PENGARUH CITA RASA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN AYAM GEPREK JUNIOR CABANG PEKAT DI KABUPATEN SUMBAWA: Indonesia - Andi Jamal; Sherwin Ary Busman (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2021)
This study aims to examine the effect of taste and location on purchasing decisions for Ayam Geprek Junior. Primary data is used for sampling with purposive sampling technique. Quantitative method while the sample in this study amounted to 100 respondents. The data obtained by the spread of the questionnaire measured by the Liker scale. The models used in the data analysis are instrument test, classical assumption test, multiple linear regression analysis and hypothesis testing. The analytical tool used in this study is SPSS 20. The results of this study indicate that: 1) Taste has a positive and significant effect on purchasing decisions. 2) Location has a positive and significant effect on purchasing decisions.